COMPETITIVE IMPACT OF FOREIGN BANKS ON FINANCIAL MARKETS IN TRANSITIONAL ECONOMIES: THE CASE UKRAINE - Shevchenko, volodymyr (Ekonomika, 2009)
The scale, the major economic indicators and the competitive impact of foreign banks on the national banking system of a transitional economy, based on the case of Ukraine, are studied. The banking sector development of the transitional economies differs from that of developed countries. Transitional economies have the bank-centered financial systems with the prevailing banking sector, a rapidly growing demand for banking services, booming credit supply, weak institutional and regulatory policies causing problems with banking stability. The intensive entry of foreign banks and their increasing market share have a significant impact on banking competition and performance. The paper argues that the foreign banks’ entry by the acquisition of Ukrainian banks’ shares is competitive by nature (demand-side competition and supply-side competition on the entry stage and post-entry market competition). The entry competition influences the relatively high price indicators of the Ukrainian banks shares in comparison with neighbouring countries. The post-entry competitive position of foreign banks is based on utilizing their competitive advantages and the post-entry market strategy. The foreign banks utilize capabilities to increase capitalization, assets and liabilities management and gaining a substantial market position, and offer more competitive products and services in all major market segments.</